Naga [videorecording] legacy of faith. ([S.l.] VTR Cassette Project Nationwide Info-Educational Dissemination Project)
Footages of the history, culture, traditions and industries of Naga.
Keywords: Naga City (Camarines Sur).; Geography; Philippine history